The Swedish version of the BRIEF2: : psychometric properties and age- and gender-related differences in executive functioning across multiple informants - Ilahi, Frida; Hoff, Eva; Daukantaité, Daiva (Child Neuropsychology, 2025)
This study evaluated the psychometric properties of the Swedish version of the Behavior Rating Inventory of Executive Function – Second Edition (BRIEF2) across self-, parent-, and teacher-report forms in a gender- and age-balanced community sample of Swedish youth. We examined factor structure, internal consistency, inter-rater reliability, measurement invariance, and age- and gender-related differences in behavioral executive functioning (EF). Participants included 1,257 adolescents (51.8% girls, aged 11–18) who completed the self-report version, 1,340 parents who completed parent reports on their children (46.7% girls, aged 5–18), and 38 teachers who provided teacher reports for 510 adolescents (58.4% girls, aged 13–18). Results supported the original three-factor model (Behavioral, Emotional, and Cognitive Regulation) across all informants, although model fit was somewhat weaker for teacher ratings. Internal consistency ranged from acceptable to excellent. Measurement invariance across age and gender was largely supported, though some scalar non-invariance was observed. Patterns of age- and gender-related differences varied by informant. Specifically, adolescents reported more EF difficulties with increasing age, whereas parents and teachers reported fewer EF difficulties in older youth. Girls self-reported greater EF difficulties, while parents and teachers generally rated girls as having less difficulty – except in the domain of Emotional Control. However, all observed gender and age differences across informants were small in magnitude. Overall, the findings support the Swedish BRIEF2 as having solid psychometric properties across the self-, parent-, and teacher-report forms. However, minor structural inconsistencies, informant discrepancies, the small teacher sample, and signs of item redundancy suggest areas for future improvement and refinement.